Arthrodesis with Retrograde Intramedullary Nail for Recurrent Infected Total Knee Arthroplasty with Patellar Tendon Rupture: A Case Report and Literature Review. Issue 5 (28th May 2020) - Liao, Chi-Yang; Lin, Chun-Li
Patellar tendon rupture after total knee arthroplasty is a rare, but often catastrophic complication. In addition, infection is also a dreaded complication after total knee arthroplasty. We report an 84-year-old female that has late infected total knee arthroplasty with patellar tendon rupture treated with resection arthroplasty and then subsequent arthrodesis with retrograde intramedullary nail. Case Presentation: The 84-year-old female underwent left total knee arthroplasty 2 years ago and revision arthroplasty last year after trauma. She presented to the emergency department with painful disability of left knee. The septic arthritis of left knee was confirmed by bacterial culture through arthrocentesis which yielded methicillinsensitive staphylococcus aureus. Patellar tendon rupture was also noted by loss of extension mechanism and patella alta in plain films. Despite attempts on open debridement and parenteral antibiotics, the infection did not settle. Resection arthroplasty with vancomycin- impregnated cement spacer implantation was performed following by 4-week parenteral antibiotics therapy. The ESR and CRP level of serum improved gradually. Arthrodesis of left knee with retrograde locking intramedullary femoral nail through single incision of the knee was performed. Protected weight bearing was allowed in one week after arthrodesis. The patient discharged 2 weeks later without recurrent infection, but leg length discrepancy about 2cm was noted. Discussion: Patellar tendon rupture after total knee arthroplasty is a rare but disabling complication whose management is often difficult. It was reported that incidence of patellar tendon rupture in literature varies between 0.3- 12.4% for primary total knee arthroplasty and between 1-15% for revision total knee arthroplasty. Contributing factors are excessive dissection and knee manipulation, and trauma. In the literature, various different operative techniques and rehabilitation programs have been described indicating the lack of a golden standard treatment protocol. However, in patients with a total knee arthroplasty, the results have been discouraging. Reconstruction of the patellar tendon can be utilized semitendinosus-gracilis graft with an interference screw and a staple fixation in treating acute ruptures, whereas allografts and synthetic mesh are indicated for chronic cases. Nevertheless, treatment outcomes for ruptured patellar tendon are not good. Gold standard treatment of infected total knee arthroplasty was resection arthroplasty with antibiotic-impregnated bone cement spacer and parenteral antibiotics therapy and then second stage revision total knee arthroplasty until the infection is eradicated. The patella tendon repair and second revision arthroplasty were not suggested by Jake et al. Patellar tendon rupture is best treated with primary repair, but infected prosthetic knee with patellar tendon rupture seemed to be more difficult to manage. Arthrodesis but not revision arthroplasty may be the best choice after infection control to improve the patient's level of function.